Georgia Architectural and Historic Properties Survey of Rural [256] South western section of the county, Valdosta, Ga. December 1980 - Smith and Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of Rural [256] South western section of the county, Valdosta, Ga. December 1980. A one story rectangular plan with gabled roof and unpainted clapboard siding. Shed porch with square posts. Sash windows with 6/6 lights. Exterior chimney, brick piers. Date of Construction: c. 1910. A typical vernacular house common to these rural areas of Brooks County.
Georgia Architectural and Historic Properties Survey of Rural [256] South western section of the county, Valdosta, Ga. December 1980. 1 electronic record and assets. Digitized from originals. 1 PDF. 3 scans. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 1.11 MB (1,173,978 bytes).
Keywords: Historic buildings; Real property surveys; Brooks County (Ga.); Lowndes County Historical Society (Lowndes County, Ga.); Valdosta (Ga.)